Acute myelogenous leukemia : genetics, biology and therapy - Alatrash, Gheath (Cancer treatment and research / series editor Steven T. Rosen, Robert H. Lurie, 2010)
Acute myelogenous leukemia (AML), is the most common form of leukemia in adults. AML is a deadly form of malignancy, the prognosis for which has not improved in the last two decades. More importantly, it is a malignancy that is seen in older adults, therefore the number of cases is likely to rise as the population ages. Over the past 15 years, genetic mechanisms underlying AML have begun to unfold. Additional research in this area has helped identify key components and characteristics. Consequently, targeted therapy of AML is receiving much attention. It is the hope of researchers that as with chronic myelogenous leukemia (CML), and the drug, Gleevec, a targeted therapy for AML will be discovered.